The Calcutta Quran Petition - Chopra , Chandmal; Chopra, Chandmal; Goel, Sita Ram. (New Delhi : Voice of India, 1987)
Comprises the text of the writ petition by Chandmal Chopra to the High Court at Calcutta and the judgement, and a detailed article by Sita Ram Goel on Islam and Muslims in India.
Keywords: Islam; Hinduism; Islam and state; Offenses against religion